2004
DOI: 10.1016/j.ejcts.2004.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation after surgical revascularization: is there any difference between on-pump and off-pump?

Abstract: There is no reduction of AF rate in myocardial revascularization without cardiopulmonary bypass. However, prophylactic beta-blocker usage decreases the incidence of AF after both on-pump and off-pump myocardial revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
(28 reference statements)
4
18
0
Order By: Relevance
“…Biomarkers indicating infl ammatory status, such as baseline C-reactive protein level, postoperative elevation of interleukin-6, and white blood cell count have been reported as independent predictors of AF following both conventional CABG and OPCAB [13][14][15]. However, only advancing age has consistently been shown to be associated with the development of postoperative AF following both conventional CABG and OPCAB [3,5,8,9]. Consequently, we examined independent predictors of postoperative AF following OPCAB from the viewpoint of left ventricular (LV) function.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Biomarkers indicating infl ammatory status, such as baseline C-reactive protein level, postoperative elevation of interleukin-6, and white blood cell count have been reported as independent predictors of AF following both conventional CABG and OPCAB [13][14][15]. However, only advancing age has consistently been shown to be associated with the development of postoperative AF following both conventional CABG and OPCAB [3,5,8,9]. Consequently, we examined independent predictors of postoperative AF following OPCAB from the viewpoint of left ventricular (LV) function.…”
Section: Discussionmentioning
confidence: 97%
“…Although a recent metaanalysis showed OPCAB signifi cantly reduced the incidence of postoperative AF compared with conventional CABG [6], the incidence of postoperative AF following OPCAB has been reported to remain high, at 21%-32% [2,3,[7][8][9]. Several factors, including low ejection fraction, and cardiac arrest have been reported as predictors of postoperative AF following conventional CABG [5,[10][11][12]. On the other hand, some perioperative factors have also been reported to be predictors of postoperative AF following OPCAB [7,8,13].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…He also observed that prophylactic -blocker usage decreased the incidence of AF after both on-pump and off-pump myocardial revascularization. 13 According to the results of many opposing studies related to postoperative AF following CABG or OPCAB surgery, a large, multicenter study should be performed in order to clear this problem up finally. 12,13 Our preliminary results partially confirmed the results obtained by other authors; however, some risk factors are completely new and oppose the outcomes above.…”
Section: Discussionmentioning
confidence: 99%
“…As such, off-pump CABG (OPCAB) is believed to elicit less systemic inflammation than on-pump surgery because of reduced cytokine responses and less myocardial injury (22). However, the association between OPCAB and a lower incidence of atrial arrhythmias were not confirmed by several studies suggesting that surgical stress is more important triggering of POAF than systemic inflammation (22). These results need to interpretation because some of these have a retrospective design with small sample size, and that they all showed at least a nonsignificant trend towards lower AF incidence in off-pump surgery.…”
Section: Discussionmentioning
confidence: 99%